The Analysis of Determinants of Compliance in Mandatory Manpower Report with Theory of Planned Behavior and Institutional Theory - Kamelia Madania Hamdie; Tri Ramaraya Koroy; Zainal Arifin; Muslim Muslim; Tommi Naviri (Journal of International Conference Proceedings, 2022)
According to the regulations, employers are required to comply with reporting procedures, which include the mandatory manpower reports (Wajib Lapor Ketenagakerjaan di Perusahaan/WLKP) that have to be submitted online. Whether establishing,Â closing, dissolving, re-opening or transferring their business, every company in Indonesia is mandated to submit their mandatory manpower report. This study aims to analyze the determinants of compliance in mandatory manpower report using the theory of planned behavior and institutional theory. The research method was explanatory research. The population in this study were companies in South Kalimantan Province that have been registered in the online WLKP system by taking 135 samples based on the purposive sampling method. Data analysis using Structural Equation Modeling (SEM) based Partial Least Square (PLS) with Smart-PLS 02 program. The results showed that the theory of planned behavior can be used to predict determinants of compliance in WLKP where attitudes and perceived behavioral control had a significant effect on compliance intention. Institutional theory did not show a significant effect on WLKP reporting compliance where normative pressure only had a marginally significant effect on compliance intention.Â Keywords: Compliance, mandatory to report employment in the company, Theory of Planned Behavior, Theory of Institutional